Announcement Effect of Dividend in Presence of Dividend Tax: Possible Agency Problem and Macro Level Inefficiency?. (December 2014) - Datta, Debabrata; Ganguli, Santanu K.; Chaturvedi, Manu
This article evaluates the efficiency of existing dividend distribution tax in India from the perspective of investors' preference pattern, as revealed in the market. It investigates the announcement effect of dividend in India in the presence of dividend distribution tax with specific legislative intent of discouraging dividend distribution. Using data on large profitable firms, we show that despite firm-level tax, higher dividend payout announcement leads to significant rise in share price. This implies that despite being tax-disadvantaged, investors of large profitable firms prefer higher payout, because it mitigates agency cost of retention. This shows that dividend distribution tax is inefficient. JEL Classification: G32, G35